Influenţe ale literaturii patristice în a doua Predoslovie a „Psaltirii” de la Alba Iulia (1651) - Florentina Nicolae (Revista de Istorie și Teorie Literară)
In this study there is analyzed the impact of patristic literature on the first translation into Romanian of the Book of Psalms, in 1651, under the coordination of Simion Ştefan, the Orthodox Metropolitan of Transylvania. The translation was done from Hebrew, but the influence of the Greek Septuagint, the Latin (not necessarily the Vulgate) and the Slavic versions cannot be ignored. In the Second Introduction (Predoslovie), the Archbishop gives an erudit presentation of the origin, authorship, aims, structure, main ideas of the Book of Psalms, using – with or without specific nomination – the works of Basil the Great, Jerome, Augustine and of the less known Byzantine writer Euthimius Zigabenus. The Western manner of quotation and paraphrase is obvious, having as a result a very modern and scientific version of the Book of Psalms.